Leaders as role models: Effects of leader presenteeism on employee presenteeism and sick leave - Dietz, Carolin; Zacher, Hannes; Scheel, Tabea; Otto, Kathleen; Rigotti, Thomas (Work and stress, 2020)
There is a broad consensus that associations exist between leadership behaviour and employee health. However, much less is known about potential mediating processes underlying links between specific leader behaviours, for instance presenteeism (i.e. working while being ill), and indicators of employee health, such as sick leave. Integrating theories of social information processing, social learning, and the allostatic load hypothesis, we propose that employee presenteeism mediates the positive association between leader presenteeism and employee sick leave. This hypothesis was tested with a multilevel mediation model using three-wave longitudinal data from 74 leaders and their 412 team members across a time period of 22 months. As hypothesised, leader presenteeism had a positive effect on employee presenteeism which, in turn, had a positive effect on employee sick leave, controlling for baseline measures of employee presenteeism and sick leave, as well as employee general health status, shared workload and job autonomy, and demographic characteristics. Additionally, leader presenteeism had a positive indirect effect on employee sick leave through employee presenteeism. These results contribute to the occupational health psychology literature by suggesting that leader health-related behaviour can have consequences for employee health-related behaviour and employee health.